Responsive cellulose nanocrystal‐based liquid crystals: From structural color manipulation to applications - Jiao Liu; Ye‐Ming Qing; Jun‐Jie Wu; Jing‐Qi Tian; Chi‐Bo Feng; Xin‐Yu Zhou; Yun Ma; Bing‐Xiang Li; Yan‐Qing Lu; Quan Li (Responsive Materials)
Abstract Cellulose, one of the most versatile and abundant biopolymers in nature, has been employed by humans for thousands of years in diverse applications, such as renewable energy resources, structural materials, and fabric constituents. Cellulose nanocrystals (CNCs), obtained through the acidic hydrolysis of cellulose‐based materials including wood, cotton, and additional sources, have attracted significant attention in areas, for example, energy storage, cosmetics, and medical devices. CNCs can spontaneously assemble into a cholesteric liquid crystal phase, which exhibits distinctive properties including biodegradability, high surface area, low cost, excellent mechanical strength, and surface functionality. Modifying the surfaces of CNCs or embedding CNCs with other materials enables novel cellulose‐based composites for advanced technologies and applications. This review systematically outlines the preparation of cellulose‐based liquid crystals (LCs), highlights the structural color regulation, photonic properties manipulation, and potential applications. Specifically, stimuli responsiveness, for example, temperature‐responsiveness, humidity‐responsiveness, pressure‐responsiveness, tension‐responsiveness, electricity‐responsiveness, magnetic force‐responsiveness and the optical properties of cellulose‐based LCs (circularly polarized light modulation and circularly polarized phosphorescence properties) are demonstrated. Furthermore, the applications of cellulose‐based LCs for gas detection, anticounterfeiting, multicolor separation, multifunctional E‐skin, and advanced fabrics are also reviewed. Finally, this review concludes with the remaining challenges and perspectives for unleashing new possibilities in the development of high‐performance multiple‐responsive cellulose‐based LCs.